2012
DOI: 10.1159/000338098
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-Associated Urinary Tract Dysfunction: An Underrecognized Clinical Entity

Abstract: Introduction: The use of ketamine as a recreational drug is on the increase among young adults attending clubs and parties. Recreational ketamine users have anecdotally reported increased lower urinary tract symptoms while using the substance. Methods: We describe the severe lower urinary tract symptoms experienced in 6 patients with chronic recreational ketamine use. We obtained a detailed history and physical examination along with further investigation to identify a relationship between recreational ketamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…The symptoms associated with the uropathic effects were mainly severe urgency, urinary frequency, intermittent hematuria, nocturia, dysuria, and bladder pain [56][57][58][59]. The duration and dosage of ketamine were proposed to be related to an increase in urinary tract dysfunction [58,60].…”
Section: Uropathic Effects Of Ketaminementioning
confidence: 99%
“…The symptoms associated with the uropathic effects were mainly severe urgency, urinary frequency, intermittent hematuria, nocturia, dysuria, and bladder pain [56][57][58][59]. The duration and dosage of ketamine were proposed to be related to an increase in urinary tract dysfunction [58,60].…”
Section: Uropathic Effects Of Ketaminementioning
confidence: 99%
“…5 The typical clinical manifestations of LUTS after long-term ketamine abuse include severe dysuria, painful haematuria, urinary urgency, urge incontinence, frequency, 1,2,7 and nocturia. 8,9 Urine cultures including searches for acid-fast bacilli in early-morning urine samples 2,10 were negative, though individuals subsequently develop concomitant urinary tract bacterial infections that are considered to be secondary. 11 A few patients present with sterile pyuria 8,12,13 or proteinuria.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…11,16 Cystoscopic findings classically associated with IC are detailed in the Table. 1,2,7,8,[10][11][12][13][16][17][18]20,24,[26][27][28][29][30][31][32][33][34][35] They include low bladder capacity, contracted bladder, marked inflammation consistent with in-situ carcinoma or significant infection, 8 severe bladder ulceration, 1,16 multiple erythematous swelling 12,13 with necrotic mucosa, 13 various degrees of epithelial inflammation with neovascularisation and petechial haemorrhages, 11 or cystitis glandularis confirmed by biopsies only. 2 It has been noted that after cystodilation or cystoscopy on filling the bladder, there may be erythematous bladder bleeding, 21 glomerulation (bladder haemorrhages) and mucosal bleeding diffusely into the lumen, 28 and even persistent active bleeding from a bladder ulcer 16 (Fig 2).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Recently, Lai et al [17] found that ketamine-associated erythematous lesions throughout the bladder were associated with lower urinary tract symptoms and mucosal injury appeared as the leading cause of symptomatology although urine cultures were sterile. If the disappearance of the trigonal whitish areas on the trigone or the normalization of the mucosal hyperemia could account for our low UTI recurrence rate is matter of discussion.…”
Section: Discussionmentioning
confidence: 99%